Gastrointestinal parasites of vervet monkeys around Lake Hawassa recreational sites, southern Ethiopia. (November 2015) - Amenu, Kebede; Tesfaye, Dawit; Tilahun, Getachew; Mekibib, Berhanu
Abstract Vervet monkeys (Chlorocebus pygerythrus ) are non-human primates belonging to the family Cercopithecidae, which are native to Africa. The objective of the present study was to assess the occurrence of gastrointestinal parasites in free-ranging vervet monkeys. A total of 140 free-ranging vervet monkeys found in the recreational areas of Hawassa city, Ethiopia, were examined for gastrointestinal parasitic infection from November 2013 to April 2014. For the identification of eggs and larvae of nematodes and cysts, oocysts and trophozoites of protozoa, faecal samples were subjected to direct smear and floatation techniques. Overall, out of 140 faecal samples examined, 75 % were found to harbour one or more gastrointestinal nematode parasites. The most frequently detected nematode parasite was hookworms (45.7 %). Parasite eggs suggestive of cestode parasites were found in 7.9 % of the samples. Coccidia were the most commonly detected protozoa parasites (27.1 %). Mixed infections with two or more parasites were detected in 74.3 % of the examined faecal samples. The present study can give baseline information on the occurrence of parasitic infection in wild vervet monkeys in the area. Future studies in the area should focus not only on the animals but also on the determination of the possible transmission of the parasites to humans which do have close interaction with the vervet monkeys.